TRANSFORMATION OF ISLAMIC EDUCATION MANAGEMENT-BASED FORMAL EDUCATION GOVERNANCE: AN INTEGRATIVE MODEL OF INSTITUTIONAL RECOGNITION, QUALITY, AND IDENTITY - Ahmad Sufyan; Subaidi Subaidi; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This article develops a conceptual governance model for formal education in pesantren from the perspective of Islamic Education Management. The study responds to a phenomenological gap in which stronger legal recognition of pesantren has not automatically produced quality-oriented, accountable, and identity-sensitive governance. Using qualitative library research, the article analyzes official regulations, books, and recent journal articles through document analysis and thematic synthesis. The findings show that governance transformation involves six interconnected dimensions: institutional legality, curriculum integration, human resources, quality assurance, financing, and public accountability. The values of tauhid, amanah, syura, adil, ihsan, and maslahah operate as ethical controls and managerial principles. The proposed model consists of institutional diagnosis, strategic planning, participatory implementation, and continuous evaluation. The article contributes an integrative framework that links legal recognition, quality governance, and pesantren identity so that formalization strengthens, rather than weakens, the educational character of pesantren.